Coated asphalt as well as preparation method and application thereof
By refining, vacuum distilling, oxidizing, and stripping devolatilization of catalytic cracking slurry, coated bitumen with high softening point and low quinoline insoluble content is prepared, solving the problems of low softening point and high quinoline insoluble content in existing technologies, reducing costs, simplifying operation, and improving safety and performance.
Patent Information
- Application Number
- CN202410716532.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-04
- Publication Date
- 2025-12-05
AI Technical Summary
Existing technologies for preparing coated asphalt suffer from problems such as low softening point, high content of quinoline insoluble substances, high cost, and complex operation, especially the production under high pressure and high temperature conditions, which carries certain risks.
A coated asphalt with high softening point and low quinoline insoluble matter was prepared by refining, vacuum distilling, oxidation, and stripping devolatilization of catalytic cracking slurry. The specific steps included vacuum distillation at 310-340℃ and 3-7kPa, oxidation at 280-360℃, and stripping devolatilization at 280-360℃ and relatively high air flow.
This technology enables the preparation of coated asphalt with high softening point and low quinoline insoluble content without adding any additives, reducing costs, simplifying the operation process, and improving product performance and safety.
Smart Images

Figure BDA0004875743190000091 
Figure BDA0004875743190000101
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium battery coated asphalt materials, specifically to a coated asphalt, its preparation method, and its application. Background Technology
[0002] As the main energy storage power source in the new energy industry, lithium-ion batteries have enormous development potential and utilization value. Due to their characteristics such as high energy density, low self-discharge, long service life, and non-toxic substances, lithium-ion batteries are widely used in industries such as mobile phones, laptops, and new energy vehicles.
[0003] Lithium-ion batteries mainly consist of four parts: positive electrode material, negative electrode material, separator, and electrolyte. Currently, lithium-ion battery negative electrode materials mainly fall into two categories: graphite negative electrode and silicon-based negative electrode material. The lithium-ion negative electrode material that has been commercially applied on a large scale is mainly graphite-based. However, graphite still has many problems at present. For example, the insertion and extraction of Li+ ions into and out of the graphite surface during charging and discharging can cause graphite shedding and structural damage. At the same time, the compatibility between electrolyte and graphite is also poor. To solve these problems, graphite negative electrodes need to be modified. Among modified graphite, pitch, as a commonly used carbon source, has always attracted much attention.
[0004] Coated bitumen, also known as high softening-point bitumen, is mainly used to cover the surface of graphite anode materials. This reduces the problem of electrode shedding caused by the volume expansion of the anode material, improves the compatibility between the graphite anode material and the electrolyte, and thus improves the reversible capacity, cycle stability, and other performance characteristics of lithium batteries. This is because high softening-point bitumen has a low content of lightweight components, resulting in less gas escape during carbonization. After high-temperature carbonization and pyrolysis, it can form a dense amorphous carbon coating (high coking value) on the graphite surface, reducing the direct contact between the graphite active surface and the electrolyte.
[0005] CN109233305A discloses a method for preparing coated asphalt by using soft asphalt as raw material, which involves centrifugation, sedimentation, flash evaporation, and mixing with coumarone. However, the softening point of the coated asphalt prepared by this method is around 110°C, which is lower than that of the coated asphalt prepared in this invention.
[0006] CN113563915A discloses a method for preparing coated asphalt by mixing purified furfural extract oil and purified catalytic cracking slurry in a certain proportion. However, this method needs to be carried out under conditions of absolute pressure of 0.5MPa to 4.5MPa and reaction temperature of 360℃ to 520℃. Production under high pressure and high temperature conditions has certain risks.
[0007] CN11442685A discloses a method for obtaining high softening point asphalt by using heavy oil as raw material, performing a pre-crosslinking reaction in the presence of catalyst toluenesulfonic acid, crosslinking agents such as trioxymethylene, benzaldehyde, and p-dimethylaldehyde, and then undergoing deep oxidative crosslinking and vacuum purging. This method requires the addition of a large amount of catalyst and crosslinking agent, which greatly increases the cost. In addition, the raw material heavy oil is a mixture of several oil slurries, and the raw material has the characteristic of instability.
[0008] CN114437557A discloses a method for preparing coated asphalt using medium-temperature coal tar pitch as raw material, mixing it with petroleum asphalt, and employing a secondary purification process and adding a modifier. This method requires mixing the raw materials and adding a certain amount of additives and catalysts to prepare the coated asphalt, which has the problems of complicated preparation and high cost. Summary of the Invention
[0009] The purpose of this invention is to prepare oil-based coated asphalt with high softening point and low quinoline insoluble content without adding any additives.
[0010] To achieve the above objectives, a first aspect of the present invention provides a method for preparing coated asphalt, the method comprising:
[0011] (1) The catalytic cracking slurry is refined to obtain a refined effluent; the refined effluent is subjected to vacuum distillation at 310-340℃ and 3-7kPa to obtain heavy component I with an initial boiling point of 450℃ or higher; the conditions of the refining process are controlled so that the sulfur content and nitrogen content in the refined effluent are <0.5wt% and <0.5wt% respectively.
[0012] (2) Under the conditions of 280-360℃ and first air flow rate, the recombinant component I is oxidized to obtain an oxidized substance;
[0013] (3) Under the conditions of 280-360℃ and second air flow, the oxidized substance is subjected to air stripping and devolatilization treatment to obtain the coated asphalt;
[0014] Relative to each 1 kg of the recombinant component I, the second airflow rate is 0.4-1.9 m³ higher than the first airflow rate. 3 / h.
[0015] A second aspect of the present invention provides coated bitumen prepared by the method described in the first aspect.
[0016] A third aspect of the present invention provides the application of the coated asphalt described in the second aspect in lithium batteries.
[0017] The solution of the present invention has at least the following advantages:
[0018] (1) The oil-based coated asphalt prepared by the method of the present invention has the advantages of high softening point, low content of quinoline insoluble substances and high coking value.
[0019] (2) The preparation method of the present invention has the advantages of low cost and simple industrial operation. Detailed Implementation
[0020] The endpoints and any values of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of the various ranges, the endpoint values of the various ranges and individual point values, and individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.
[0021] As previously described, a first aspect of the present invention provides a method for preparing coated bitumen, the method comprising:
[0022] (1) The catalytic cracking slurry is refined to obtain a refined effluent; the refined effluent is subjected to vacuum distillation at 310-340℃ and 3-7kPa to obtain heavy component I with an initial boiling point of 450℃ or higher; the conditions of the refining process are controlled so that the sulfur content and nitrogen content in the refined effluent are <0.5wt% and <0.5wt% respectively.
[0023] (2) Under the conditions of 280-360℃ and first air flow rate, the recombinant component I is oxidized to obtain an oxidized substance;
[0024] (3) Under the conditions of 280-360℃ and second air flow, the oxidized substance is subjected to air stripping and devolatilization treatment to obtain the coated asphalt;
[0025] Relative to each 1 kg of the recombinant component I, the second airflow rate is 0.4-1.9 m³ higher than the first airflow rate. 3 / h.
[0026] The refining process described in this invention is sufficient to ensure that the sulfur content and nitrogen content in the refined effluent are <0.5wt% and <0.5wt%, respectively. Those skilled in the art can make the selection according to conventional methods, and this should not be construed as a limitation of the present invention.
[0027] Preferably, the second airflow rate is 0.4-1 m³ higher than the first airflow rate per 1 kg of the recombinant component I. 3 / h. The inventors of this invention have discovered that, under these preferred conditions, the coated asphalt prepared by the method of this invention has a lower content of quinoline insolubles and a higher softening point.
[0028] Preferably, in step (3), the time for the stripping and devolatilization treatment is 3-10 hours.
[0029] Preferably, in step (3), the stirring speed of the stripping and devolatilization treatment is 60-200 rpm.
[0030] According to a particularly preferred embodiment, in step (3), the conditions for the stripping and devolatilization treatment include: a time of 3-10 hours and a stirring speed of 60-200 rpm.
[0031] Preferably, in step (2), the oxidation treatment time is 4-15 hours.
[0032] Preferably, in step (2), the stirring speed of the oxidation treatment is 60-200 rpm.
[0033] According to a particularly preferred embodiment, in step (2), the oxidation treatment conditions include: a time of 4-15 hours and a stirring speed of 60-200 rpm. The inventors of this invention have found that under these preferred conditions, the coated asphalt prepared by the method of this invention has a lower content of quinoline insolubles and a higher softening point.
[0034] Preferably, in step (2), during the oxidation treatment, the first air flow rate is 0.1-1.5 m³ / kg relative to each kg of the heavy component I. 3 / h. The inventors of this invention have discovered that, under these preferred conditions, the coated asphalt prepared by the method of this invention has a lower content of quinoline insolubles and a higher softening point.
[0035] According to a particularly preferred embodiment, the catalytic cracking slurry contains 40-80 wt% aromatics, 6-22 wt% gums, <17 wt% asphaltenes, 7-25 wt% residual carbon, <1.35 wt% sulfur, and <0.65 wt% nitrogen; and the catalytic cracking slurry has a density of 1000-1190 kg / m³ at 20°C. 3 The inventors of this invention have discovered that, under these preferred conditions, the coated asphalt prepared by the method of this invention has a lower content of quinoline insolubles and a higher softening point.
[0036] As previously stated, a second aspect of the present invention provides coated bitumen prepared by the method described in the first aspect.
[0037] Preferably, the softening point of the coated asphalt is 240-290℃, and the quinoline insoluble content is <1.5wt%.
[0038] Preferably, the coking value of the coated asphalt is ≥65wt%, and the ash content is <0.02wt%.
[0039] According to a preferred embodiment, the softening point of the coated asphalt is 240-290℃, the coking value is ≥65wt%, the ash content is <0.02wt%, and the quinoline insoluble matter in the coated asphalt is <1.5wt%.
[0040] As previously stated, the third aspect of the present invention provides the application of the coated bitumen described in the second aspect in lithium batteries.
[0041] Unless otherwise specified, all raw materials mentioned in the following examples are commercially available products.
[0042] The properties of the catalytic cracking slurry used below are shown in Table 1.
[0043] Table 1
[0044] Content (wt%) Aromatics (wt%) 63.53 Gel (wt%) 17.27 Asphalt (wt%) 10.15 Residual carbon (wt%) 17.19 <![CDATA[Density at 20 °C (kg / m 3 )]]> 1130.7 Sulfur content (wt%) 0.96 Nitrogen content (wt%) 0.41
[0045] Example 1
[0046] (1) The catalytic cracking slurry is subjected to cross-flow filtration and catalytic hydrotreating with a ceramic membrane in sequence to obtain a refined effluent with a sulfur content of 0.31 wt% and a nitrogen content of 0.19 wt%. The refined effluent is subjected to vacuum distillation at 330°C and 5 kPa to obtain heavy component I with an initial boiling point of over 450°C.
[0047] (2) At 330℃ and 0.2m 3 At a first air flow rate of / h and a stirring speed of 120rpm, 1500g of the heavy component I was oxidized for 13h to obtain an oxidized substance;
[0048] (3) At 330℃ and 1m 3 At a second air flow rate of / h and a stirring speed of 120rpm, the oxidized material was subjected to air stripping and devolatilization treatment for 6h to obtain the coated asphalt L1. The properties of the coated asphalt L1 are shown in Table 2.
[0049] Example 2
[0050] (1) The catalytic cracking slurry is subjected to cross-flow filtration and catalytic hydrotreating with a ceramic membrane in sequence for refining. The sulfur content and nitrogen content in the refined effluent are 0.31 wt% and 0.19 wt%, respectively. The refined effluent is subjected to vacuum distillation at 330°C and 5 kPa to obtain heavy component I with an initial boiling point of above 450°C.
[0051] (2) At 340℃, 2m 3At a first air flow rate of / h and a stirring speed of 120rpm, 1500g of the heavy component I was oxidized for 4h to obtain an oxidized substance;
[0052] (3) At 340℃ and 3m 3 At a second air flow rate of / h and a stirring speed of 120rpm, the oxidized material was subjected to air stripping and devolatilization treatment for 3h to obtain the coated asphalt L2. The properties of the coated asphalt L2 are shown in Table 2.
[0053] Example 3
[0054] (1) The catalytic cracking slurry is subjected to cross-flow filtration and catalytic hydrotreating with a ceramic membrane in sequence for refining. The sulfur content and nitrogen content in the refined effluent are 0.31 wt% and 0.19 wt%, respectively. The refined effluent is subjected to vacuum distillation at 330°C and 5 kPa to obtain heavy component I with an initial boiling point of above 450°C.
[0055] (2) At 340℃ and 0.8m 3 At a first air flow rate of / h and a stirring speed of 120rpm, 1500g of the heavy component I was oxidized for 8h to obtain an oxidized substance;
[0056] (3) At 340℃ and 1.4m 3 At a second air flow rate of / h and a stirring speed of 120rpm, the oxidized material was subjected to air stripping and devolatilization treatment for 5h to obtain the coated asphalt L3. The properties of the coated asphalt L3 are shown in Table 2.
[0057] Example 4
[0058] (1) The catalytic cracking slurry is subjected to cross-flow filtration and catalytic hydrotreating with a ceramic membrane in sequence for refining. The sulfur content and nitrogen content in the refined effluent are 0.31 wt% and 0.19 wt%, respectively. The refined effluent is subjected to vacuum distillation at 330°C and 5 kPa to obtain heavy component I with an initial boiling point of above 450°C.
[0059] (2) At 300℃ and 2.2m 3 At a first air flow rate of / h and a stirring speed of 120rpm, 1500g of the heavy component I was oxidized for 15h to obtain an oxidized substance;
[0060] (3) At 300℃ and 3m 3 At a second air flow rate of / h and a stirring speed of 120rpm, the oxidized material was subjected to air stripping and devolatilization treatment for 8h to obtain the coated asphalt L4. The properties of the coated asphalt L4 are shown in Table 2.
[0061] Example 5
[0062] (1) The catalytic cracking slurry is subjected to cross-flow filtration and catalytic hydrotreating with a ceramic membrane in sequence for refining. The sulfur content and nitrogen content in the refined effluent are 0.31 wt% and 0.19 wt%, respectively. The refined effluent is subjected to vacuum distillation at 330°C and 5 kPa to obtain heavy component I with an initial boiling point of above 450°C.
[0063] (2) At 355℃ and 0.2m 3 At a first air flow rate of / h and a stirring speed of 120rpm, 1500g of the heavy component I was oxidized for 8h to obtain an oxidized substance;
[0064] (3) At 355℃ and 0.8m 3 At a second air flow rate of / h and a stirring speed of 120rpm, the oxidizing material is further oxidized and stripped for 6h to obtain the coated asphalt L5. The properties of the coated asphalt L5 are shown in Table 2.
[0065] Comparative Example 1
[0066] This comparative example was conducted in a similar manner to Example 1, except that the second airflow rate in step (3) was adjusted to 0.4 m³ / s. 3 / h, the rest is the same as in Example 1, and coated asphalt DL1 is prepared. The properties of coated asphalt DL1 are shown in Table 2.
[0067] Comparative Example 2
[0068] This comparative example is conducted in a similar manner to Example 3, except that the second airflow rate in step (3) is adjusted to 1m. 3 / h, the rest is the same as in Example 1, and coated asphalt DL2 is prepared. The properties of the coated asphalt DL2 are shown in Table 2.
[0069] Comparative Example 3
[0070] This comparative example was conducted in a similar manner to Example 4, except that the second airflow rate in step (3) was adjusted to 5.2 m³ / s. 3 / h, the rest is the same as in Example 4, and coated asphalt DL3 is prepared. The properties of the coated asphalt DL3 are shown in Table 2.
[0071] Comparative Example 4
[0072] This comparative example was carried out in a similar manner to Example 1, except that the oxidation temperature in step (2) was 270°C, and the rest was the same as in Example 1. Coated asphalt DL4 was prepared, and the properties of the coated asphalt DL4 are shown in Table 2.
[0073] Comparative Example 5
[0074] This comparative example was carried out in a similar manner to Example 1, except that the oxidation temperature in step (2) was 375°C, and the rest was the same as in Example 1. Coated asphalt DL5 was prepared, and the properties of the coated asphalt DL5 are shown in Table 2.
[0075] Comparative Example 6
[0076] This comparative example was conducted in a similar manner to Example 1, except that the temperature of the stripping and devolatilization treatment in step (3) was 270°C, and the rest was the same as in Example 1. Coated asphalt DL6 was prepared, and the properties of the coated asphalt DL6 are shown in Table 2.
[0077] Comparative Example 7
[0078] This comparative example was carried out in a similar manner to Example 1, except that the temperature of the stripping and devolatilization treatment in step (3) was 375°C, and the rest was the same as in Example 1. Coated asphalt DL7 was prepared, and the properties of the coated asphalt DL7 are shown in Table 2.
[0079] Comparative Example 8
[0080] This comparative example was conducted in a similar manner to Example 1, except that the air in step (3) was replaced with nitrogen gas of equal flow rate. The rest was the same as in Example 1. Coated asphalt DL8 was prepared, and the properties of the coated asphalt DL8 are shown in Table 2.
[0081] Comparative Example 9
[0082] This comparative example was carried out in a similar manner to Example 1, except that the air in step (3) was replaced with water vapor of equal flow rate. The rest was the same as in Example 1, and coated asphalt DL9 was prepared. The properties of the coated asphalt DL9 are shown in Table 2.
[0083] Table 2
[0084]
[0085]
[0086] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.
Claims
1. A process for preparing a bitumen-coated product, characterized in that, The method comprises: (1) subjecting catalytic cracking slurry oil to a refining treatment to obtain a refined effluent; subjecting the refined effluent to a vacuum distillation treatment at 310-340℃ and 3-7kPa to obtain a heavy component I with an initial boiling point of 450℃ or higher; and controlling the conditions of the refining treatment so that the sulfur content in the refined effluent is <0.5wt%, and the nitrogen content is <0.5wt%; (2) subjecting the heavy component I to an oxidation treatment at 280-360℃ and a first air flow rate to obtain an oxidized substance; (3) subjecting the oxidized substance to a gas stripping devolatilization treatment at 280-360℃ and a second air flow rate to obtain the coated pitch; The second air flow rate is higher than the first air flow rate by 0.4-1.9 m3 / h per 1 kg of the heavy component I 3 / h.
2. The method of claim 1, wherein, The second air flow rate is higher than the first air flow rate by 0.4-1 m3 / h per 1 kg of the heavy component I 3 / h.
3. The method according to claim 1 or 2, characterized in that, In step (3), the gas stripping devolatilization treatment is performed for 3-10h.
4. The method according to claim 1 or 2, characterized in that, In step (3), the stirring speed of the gas stripping devolatilization treatment is 60-200rpm.
5. The method according to any one of claims 1 to 4, characterized in that, In step (2), the oxidation treatment is performed for 4-15h.
6. The method according to any one of claims 1 to 4, characterized in that, In step (2), the stirring speed of the oxidation treatment is 60-200rpm.
7. The method according to any one of claims 1 to 6, characterized in that, In the oxidation treatment in Step (2), the first air flow rate is 0.1 to 1.5 m3 / h per 1 kg of the heavy component I. 3 / h.
8. The coated pitch prepared by the method of any one of claims 1-7.
9. The coated bitumen of claim 8, wherein, The coated pitch has a softening point of 240-290℃, and a quinoline insoluble content of <1.5wt%.
10. The coated bitumen according to claim 8 or 9, characterized in that, The coated pitch has a coking value of ≥65wt%, and an ash content of <0.02wt%.
11. The coated pitch of any one of claims 8-10 for use in lithium batteries.
Citation Information
Patent Citations
Preparation method of coated asphalt for carbon cathode material
CN109233305A
Preparation method of coated asphalt
CN113563915A
Preparation method of high-softening-point coated asphalt for lithium ion battery negative electrode material
CN114437557A